PERSEPSI CALON PENGANTIN TERHADAP TES KESEHATAN DAN PELAKSANAAN KONSELING PRA-NIKAH DI PUSKESMAS MEDANG KAMPAI KOTA DUMAI - Elfiani; Saam, Zulfan; Delvis, Yesica (Jurnal Doppler, 2022)
Introduction: The high number of HIV/AIDS cases in Indonesia and several regions including Riau Province requires the local government of Dumai City to reduce the number of Sexually Transmitted Diseases by requiring every bride and groom to have a premarital health test. Objective: To determine the perception of the prospective bride and groom on the medical test and the implementation of pre-marital counselling. Methods: The type of research is Mix methods, quantitative and qualitative. The research subjects of the prospective bride and groom at the Medang Kampai Health Center were 30 pairs of prospective brides and grooms. Quantitative data collection techniques by distributing questionnaires by looking at perceptions of vulnerability, seriousness, change, benefits and obstacles, taking action. Collecting qualitative data using in-depth interviews with three informants. Results: There were 30 pairs of prospective brides, the majority 85% of respondents who were prospective brides agreed to test for HIV/AIDS, while for the syphilis test, the majority of respondents, namely 60%, were still in doubt and did not agree. Respondents' perceptions of pregnancy tests as much as 70% agreed to take a pregnancy test before marriage. Meanwhile, for the categories of perceptions of vulnerability, seriousness, changes, benefits and obstacles as well as perceptions of taking action, the majority of respondents answered the moderate category as much as 48.3% to 70%. Conclusion: Of the 30 pairs of prospective brides, only a few people were hesitant to do premarital testing and counselling, but after being approached, they finally wanted to do a health test.